What's next for the Sustainable Development Goals? Synergy and trade-offs in affordable and clean energy (SDG 7) - Brindha Ramasubramanian; Seeram Ramakrishna (Sustainable Earth Reviews)
Abstract This Sustainable Development Goal (SDG 7) analysis addresses critical challenges through three questions, backed by literature and evidence. Environmental, social, and governance concerns were discussed. A notable SDG target shortfall was observed from International Renewable Energy Agency, International Energy Agency, and United Nation’s publications. Urgent actions include refining greenhouse gas emission equivalent estimations and establishing unified life cycle assessment standards. While prioritizing renewables, minimizing dependence on non-renewables for a lower carbon footprint is vital. Balancing energy production with per capita consumption reduction, especially with a growing population, is key to achieving net-zero emissions. This solution demands a thoughtful evaluation of challenges tied to specific renewable technologies and their socio-economic impact. Balancing economic growth, crisis response, and resource management is crucial for acheiving SDG 7 targets.